2011
DOI: 10.1002/ceat.201000312
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐Assisted Chemoselective Hydrogenation Reactions Incorporating Hydrogen as Reducing Agent

Abstract: The use of modern microwave equipment affords an easy and safe handling in the laboratory routine. The described quartz reactor system was tested in different reaction types to show its versatile applications. Various liquid-phase hydrogenations were carried out successfully. The construction of the reactor allows the direct introduction of gases into the reaction mixture so that the reduction can be performed with gaseous hydrogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 53 publications
(42 reference statements)
0
16
0
Order By: Relevance
“…The glasses were decorated with different metal precursors using a wet impregnation methodology. Benzalacetophenone [14] and verbenone [15] were employed as substrates for the investigation of reaction parameters such as hydrogen pressure, reaction temperature, reaction time, and type of metal. Hydrogenation reactions were carried out in ethyl acetate as solvent using a microwave-autoclave system allowing a maximum operating pressure of 1.0 MPa H 2 [15].…”
Section: Hydrogenation Of C=c Double Bondsmentioning
confidence: 99%
See 2 more Smart Citations
“…The glasses were decorated with different metal precursors using a wet impregnation methodology. Benzalacetophenone [14] and verbenone [15] were employed as substrates for the investigation of reaction parameters such as hydrogen pressure, reaction temperature, reaction time, and type of metal. Hydrogenation reactions were carried out in ethyl acetate as solvent using a microwave-autoclave system allowing a maximum operating pressure of 1.0 MPa H 2 [15].…”
Section: Hydrogenation Of C=c Double Bondsmentioning
confidence: 99%
“…Benzalacetophenone [14] and verbenone [15] were employed as substrates for the investigation of reaction parameters such as hydrogen pressure, reaction temperature, reaction time, and type of metal. Hydrogenation reactions were carried out in ethyl acetate as solvent using a microwave-autoclave system allowing a maximum operating pressure of 1.0 MPa H 2 [15]. Experiments with both substrates revealed that the conversion increases with increasing pressure, temperature, and reaction time [14,15].…”
Section: Hydrogenation Of C=c Double Bondsmentioning
confidence: 99%
See 1 more Smart Citation
“…to citronellal over Pd catalysts through the tuning of the reaction conditions [12][13][14] and the selection of different supports, including Al 2 O 3 , zeolite, CaCO 3 , TiO 2 , and sepiolite. [15][16][17][18] However, the selectivities to the desired products over these catalysts are not promising, likely because of the poor selectivity of Pd for the hydrogenation of C=C and C=O.…”
Section: Introductionmentioning
confidence: 98%
“…24 Catalytic hydrogenation under MW irradiation has been conducted safely and quickly in open vessels, 25 sealed reaction systems, 26 a quartz reactor and even under 2.5 MPa of hydrogen pressure.…”
mentioning
confidence: 99%